2017
DOI: 10.12659/msm.898522
|View full text |Cite
|
Sign up to set email alerts
|

Intermedin 1-53 Inhibits Myocardial Fibrosis in Rats by Down-Regulating Transforming Growth Factor-β

Abstract: BackgroundMyocardial fibrosis is the result of persistent anoxia and ischemic myocardial fibers caused by coronary atherosclerotic stenosis, which lead to heart failure, threatening the patient’s life. This study aimed to explore the regulatory role of intermedin 1-53 (IMD1-53) in cardiac fibrosis using neonatal rat cardiac fibroblasts and a myocardial infarction (MI) rat model both in vitro and in vivo.Material/MethodsThe Western blot method was used to detect the protein expression of collagen I and collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…In addition, IMD1-53 has an anti-fibrosis effect on lung [ 12 ] and renal fibrosis [ 13 ], and other studies have demonstrated that IMD1-53 can ameliorate fibrosis of the left ventricle (LV) in animal models of hypertension [ 14 ], MI [ 15 ], and LV hypertrophy [ 16 ]. IMD1-53 is an effective anti-fibrosis hormone that inhibits cardiac fibrosis formation after MI by downregulating the expression of TGF-β and the phosphorylation of smad3 [ 17 ]. In another study, intermedin alleviated unilateral ureteral obstruction (UUO)-induced renal fibrosis by the inhibition of Nox4 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, IMD1-53 has an anti-fibrosis effect on lung [ 12 ] and renal fibrosis [ 13 ], and other studies have demonstrated that IMD1-53 can ameliorate fibrosis of the left ventricle (LV) in animal models of hypertension [ 14 ], MI [ 15 ], and LV hypertrophy [ 16 ]. IMD1-53 is an effective anti-fibrosis hormone that inhibits cardiac fibrosis formation after MI by downregulating the expression of TGF-β and the phosphorylation of smad3 [ 17 ]. In another study, intermedin alleviated unilateral ureteral obstruction (UUO)-induced renal fibrosis by the inhibition of Nox4 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%